Longitudinal Assessment of Botulinum Toxin Treatment for Lateral Trunk Flexion and Pisa Syndrome in Parkinson’s Disease: Real-life, Long-Term Study - Claudia Ledda; Elisa Panero; Ugo Dimanico; Mattia Parisi; Marialuisa Gandolfi; Michele Tinazzi; Christian Geroin; Francesco Marchet; Giuseppe Massazza; Leonardo Lopiano; Carlo Alberto Artusi (Toxins, 2023)
Lateral trunk flexion (LTF) and its severe form, called Pisa syndrome (PS), are highly invalidating axial postural abnormalities associated with Parkinson’s disease (PD). Management strategies for LTF lack strong scientific evidence. We present a real-life, longitudinal study evaluating long-term efficacy of botulinum toxin (BoNT) injections in axial muscles to reduce LTF and PS in PD. A total of 13 PD patients with LTF > 5° received ultrasound- and electromyography-guided BoNT injections every 4 months. Seven untreated matched PD patients with LTF served as controls and their changes in posture after 18 months were compared with those of seven patients continuing BoNT over 12 months. 53.8% of patients continued the BoNT injections for at least 12 months. Various individual LTF responses were observed. Overall, BoNT-treated patients obtained a not statistically significant improvement of LTF of 17 ± 41% (p = 0.237). In comparison, the seven untreated PD patients suffered a deterioration in LTF over 12 months by 36 ± 45% (p = 0.116), showing a significantly different trajectory of posture change (p = 0.026). In conclusion, repeated BoNT injections in axial muscles showed varying effects in managing PD-associated LTF, suggesting that: (a) a relevant number of patients with LTF can benefit from BoNT; (b) long-term treatment could prevent LTF worsening; (c) an instrumented, personalized approach is important; and (d) there is a need for prospective, long-term studies.